2021
DOI: 10.1159/000515910
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Intestinal Barrier to Prevent Gut-Derived Inflammation and Disease: A Role for Intestinal Alkaline Phosphatase

Abstract: <b><i>Background:</i></b> Intestinal alkaline phosphatase (IAP) as a tissue-specific isozyme of alkaline phosphatases is predominantly produced by enterocytes in the proximal small intestine. In recent years, an increasing number of pathologies have been identified to be associated with an IAP deficiency, making it very worthwhile to review the various roles, biological functions, and potential therapeutic aspects of IAP. <b><i>Summary:</i></b> IAP primarily orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…IAP is ubiquitously expressed by enterocytes in the proximal small intestine and exists in high concentrations within luminal vesicles secreted by enterocytes on the brush border of the microvilli. 133 IAP is secreted bilaterally and is also released in small amounts into the blood. 134 IAP plays an important anti-inflammatory role by dephosphorylating potentially pro-inflammatory ligands such as adenosine triphosphate (ATP), uridine diphosphate (UDP), unmethylated cytosine-guanosine dinucleotides (CpG), and LPS.…”
Section: Intestinal Alkaline Phosphatasementioning
confidence: 99%
“…IAP is ubiquitously expressed by enterocytes in the proximal small intestine and exists in high concentrations within luminal vesicles secreted by enterocytes on the brush border of the microvilli. 133 IAP is secreted bilaterally and is also released in small amounts into the blood. 134 IAP plays an important anti-inflammatory role by dephosphorylating potentially pro-inflammatory ligands such as adenosine triphosphate (ATP), uridine diphosphate (UDP), unmethylated cytosine-guanosine dinucleotides (CpG), and LPS.…”
Section: Intestinal Alkaline Phosphatasementioning
confidence: 99%
“…112 In normal mice, IAP supplementation effectively alleviated aging caused by intestinal barrier function destruction, restored metabolic dysfunction and microbiome disorders, and prolonged life spans through LPS inactivation. 113 Liu et al demonstrated the effective alleviation of liver fibrosis by endogenous IAP, which was mainly associated with intestinal barrier function maintenance through TLR4mediated mechanisms. 15 In addition to LPS, IAP dephosphorylates other potential pro-inflammatory ligands such as ATP, UDP, and CpG and microbial associated molecular patterns activate TLR 2, 3, 5, and 9 in immune and epithelial cells, 114 thereby inducing downstream inflammatory responses.…”
Section: Improvement Of Local or Systemic Inflammatory Statusmentioning
confidence: 99%
“…Danielak et al found that IAP supplementation and voluntary exercise effectively inhibited the expression of TNF-α, IL-1β, and IL-6 in a colitis mouse model fed with a standard diet or HFD . In normal mice, IAP supplementation effectively alleviated aging caused by intestinal barrier function destruction, restored metabolic dysfunction and microbiome disorders, and prolonged life spans through LPS inactivation . Liu et al demonstrated the effective alleviation of liver fibrosis by endogenous IAP, which was mainly associated with intestinal barrier function maintenance through TLR4-mediated mechanisms …”
Section: Intestinal Barrier Protection By Iapmentioning
confidence: 99%
“…inflammatory bowel disease (IBD) and type-2 diabetes. It appears that IAP supplementation may have therapeutic potential in the treatment of these conditions by reducing inflammation and protecting the gut barrier [ 9 ]. In addition, evidence to reveal that IAP may play a role in the regulation of mineral metabolism, although more research is needed in this area.…”
Section: Introductionmentioning
confidence: 99%